Implementasi Sains Islam Dalam Pembelajaran Pendidikan Agama Islam Di Perguruan Tinggi Umum - Nurhilaliyah (CV. SINAR HOWUHOWU, 2026)
A learning approach that can comprehensively integrate Islamic values with science needs to be implemented in order to address the dynamics of education in today’s era of scientific and technological advancement. Research was conducted to examine the integration of science Islam in Islamic Religious Education (PAI) courses at public universities and its impact on student character development, given the ongoing separation between general knowledge and religious studies, which hinders the full realization of the learning process. A qualitative approach was adopted in this research through a literature review of scientific journals published in the last five years. The findings of the research indicate that the integration of science Islam can be implemented through the formulation for comprehensive learning objectives, the development of contextual teaching materials, the use of active and participatory learning methods, and an evaluation system that incorporates psychomotor, affective, and cognitive. This integrative approach has been proven to have a positive impact on students’ character formation, including increased moral awareness, enhanced critical and reflective thinking skills, and the strengthening of spiritual values and social responsibility. However, its implementation still faces several challenges, such as limited lecturer competence, a lack of integration-based teaching materials, and suboptimal institutional support. Therefore, systematic and sustainable efforts are required to optimize the integrated application of science Islam in PAI courses at public universities.